An Assessment of Sectoral Dynamics and Employment Shift in Indian and Chinese Economy. (September 2016) - Khan, Waseem; Fatima, Sana
This study has analysed structural transformation and inter-sectoral relationships of the Indian and the Chinese economy. Variation in employment dynamics across the sectors and growth instability is also examined by taking data from the World Development Indicators (WDI, 2015) of the World Bank. The study has revealed that there is a gradual decline in agriculture in both the countries. Both the economies are now concentrating at service sectors. China is fully exploiting its industrial sector potential while India has been lagging behind in this sector. Johansen's cointegration approach revealed the existence of one cointegration relationship among all the three sectors, namely, agricultural, industrial and services, at 5 per cent level of significance for both the countries. A passive employment shift has been seen from agriculture to non-agriculture sector in India. Occupational transformation in China is faster than India. Policy makers should focus on job generation, especially in services and labour intensive manufacturing sector in India. China should try to create jobs in industrial and services sector because agriculture sector has been sharply declining and is still carrying huge load of employment.